Perbandingan Latihan Dengan Menggunakan Pendekatan Taktis dan Teknis Terhadap Keterampilan Passing Controling Pada Peserta Ekstrakurikuler Futsal di SMPN 1 Purwasari - Fathurrohman, Muhammad; Salam, Abdul; Iqbal, Rahmat (Peneliti.net, 2023)
The goal of this study was to compare training with a tactical approach and training with a technical approach to passing controlling futsal abilities in futsal extracurricular activities at SMP Negeri 1 Purwasari. This is a quantitative study using an experimental method on futsal extracurricular participation at SMP Negeri 1 Purwasari, Karawang Regency in 2023. There are 20 persons in the population and 20 people in the sample. Total sampling was employed as the sample strategy. Passing stopping was the research instrument used to assess passing controlling abilities. Data study reveals that (1) tactical approach training influences passing controlling skills. (2) A technical approach to training influences passing controlling skills. (3) When it comes to passing managing skills, training with a tactical approach is more beneficial than training with a technical approach. The findings lead to recommendations for enhancing basic futsal passing tactics in futsal ball games to increase passing controlling skills.